Anomalous coordination behaviour of 6‐methyl‐2‐oxo‐1, 2‐dihydroquinoline‐3‐carboxaldehyde‐4(N)‐substituted Schiff bases in Cu(II) complexes: Studies of structure, biomolecular interactions and cytotoxicity. (27th February 2019) - Elamathi, C.; Butcher, Ray; Prabhakaran, R.
Abstract : A series of copper(II) complexes containing 6‐methyl‐2‐oxo‐1, 2‐dihydroquinoline‐3‐carboxaldehyde‐derived Schiff bases have been synthesized and characterised using various analytical and spectroscopic techniques. X‐ray crystallographic analysis confirmed the true coordinating nature of ligands with copper ion. The ligands exhibited ONS tridentate neutral and monobasic coordination. The spectroscopic results evidenced the interaction of the ligands and their copper(II) complexes with nucleic acid/serum albumin. Further, the complexes showed significant activity against human skin cancer cell line (A431) and less toxicity against human keratinocyte cell line (HaCaT). Acridine orange/propidium iodide dual staining studies indicated that the major cause of A431 cell death was through necrosis. By comparing the biological activity of all the ligands, Cu(II) complexes and standard (cisplatin), complex [Cu(H‐6MOQtsc‐Ph)(H2 O)]⋅NO3 (4 ) exhibited better activity than others, the activity being arranged as follows:4  > 1  > cisplatin > 3  > 2 . Abstract : The work focuses on the synthesis and biological evaluations of heterocyclic Schiff bases and their copper(II) metallates.